Characterization of liquid–liquid mass transfer performance in a novel pore‐array intensified tube‐in‐tube microchannel. Issue 4 (27th December 2019) - Li, Wenpeng; Xia, Fengshun; Zhao, Shuchun; Zhang, Minqing; Li, Wei; Zhang, Jinli
Abstract: Liquid–liquid mass transfer performance of a novel pore‐array intensified tube‐in‐tube microchannel (PA‐TMC) was investigated with the water‐benzoic acid‐kerosene system. Both mass transfer efficiency ( E ) and volumetric mass transfer coefficient ( K L a ) are found to increase simultaneously with the flow rate, but decrease with total number of pores and rows. However, E increases but K L a decreases with the annular length. In particular, the pore size shows an optimal value at 0.3 mm due to the interplay problem of the radial adjacent pores. Computational fluid dynamics simulations reveal that the high kinetic energy generated by the pore‐array section plays a significant role in mass transfer process. The artificial neural network model is established to correlate K L a with the investigated parameters of PA‐TMC. The comparison of K L a with other types of contactors indicates that PA‐TMC has superior mass transfer performance and high throughput for a broad industrial application.